Critical developments and applications of swarm intelligence - Shi, Yuhui (Advances in computational intelligence and robotics (ACIR) book series, 2018)
"This book provides innovative findings in swarm intelligence, evolutionary computation, computational intelligence, optimization techniques, and their applications"--